Removal of Environmental Nanoparticles Increases Protein Synthesis and Energy Production in Healthy Humans - Antuña, Eduardo; Carlos Bermejo-Millo, Juan; Caso-Onzain, Enrique; Caso-Peláez, Enrique; Potes, Yaiza; Coto-Montes, Ana (Frontiers in Bioengineering and Biotechnology, 2022)
Currently, industrial activity causes the environmental release of nanoparticles that have multiple adverse effects on population health. There is a clear correlation between the in-crease in particulate air pollution and the increases in mortality and morbidity rates in both adults and children, which demonstrates the toxic effects of these particles. However, the effect of particle removal on healthy individuals is unknown. Thus, in this preliminary study, we showed, for the first time, how the filtering equipment that we used significantly reduced a large amount of nanoparticles in a minimum time and induced a reduction of oxidative damage in healthy individuals of both sexes after 25, 50 and 100 days of exposure. These effects led to increased protein synthesis and enhanced mitochondrial efficiency, thus resulting in a highly significant triggering of ATP synthesis. These results not only provide insight into the chronic effects that environmental nanoparticles have on individuals prior to the development of pathologies but also demonstrate a system capable of reversing nanoparticle toxicity and allowing cellular energy recovery.